Can the polynomial ( x − 1 ) ( x − 2 ) ( x − 3 ) ⋯ ( x − 1 0 0 ) − 1 be factorized into 2 non-constant polynomials with integer coefficients?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( x − 1 ) ( x − 2 ) ( x − 3 ) ⋯ ( x − 1 0 0 ) − 1 = p ( x ) q ( x ) where p(x) and q(x) are 2 non-constant polynomials with integer coefficients.
p ( 1 ) q ( 1 ) = − 1 So, either p ( 1 ) = 1 , q ( 1 ) = − 1 or p ( 1 ) = − 1 , q ( 1 ) = 1
p ( 2 ) q ( 2 ) = − 1 .So,either p ( 2 ) = 1 , q ( 2 ) = − 1 or p ( 2 ) = − 1 , q ( 2 ) = 1
Now it continues...
p ( 1 0 0 ) q ( 1 0 0 ) = − 1 .So,either p ( 1 0 0 ) = 1 , q ( 1 0 0 ) = − 1 or p ( 1 0 0 ) = − 1 , q ( 1 0 0 ) = 1 .
Each p(i) or q(i) will be ± 1 where 1 ≤ i ≤ 1 0 0 ..
We know for a polynomial p ( x ) we know ( i − j ) ∣ p ( i ) − p ( j ) where i , j are integers.Now we can find i , j with i − j > 2 , p ( i ) = 1 , p ( j ) = − 1 ,This will become i − j > 2 does not divide p ( i ) − p ( j ) = 2 .it will not satisfy above condition because p(x) is an polynomial with integer coefficients.So, there is no p ( x ) exists.This logic is also valid for q ( x ) .
Again if every p ( i ) = 1 ,then we can write the p ( x ) = ( x − 1 ) ( x − 2 ) . . . . ( x − 1 0 0 ) + 1 = ( x − 1 ) ( x − 2 ) . . . . ( x − 1 0 0 ) − 1 + 2 = p ( x ) q ( x ) + 1
That's not possible .So, there must be at least one p ( i ) = − 1 .hence we can find i , j for above logic.Same logic for q(x) also.
Again if every p ( i ) = − 1 ,then we can write the p ( x ) = ( x − 1 ) ( x − 2 ) . . . . ( x − 1 0 0 ) − 1 = p ( x ) q ( x )
That's not possible because q ( x ) will become constant polynomial. .So, there must be at least one p ( i ) = 1 .hence we can find i , j for above logic.Same logic for q(x) also.
That's why factorization is not possible.
Good approach :)
There is a slight gap towards the end. After finding p ( i ) = 1 , why must there be a j such that p ( j ) = − 1 ? Do you see how to plug that gap?
Log in to reply
I have updated m y solution.Plzz check.
Log in to reply
That's the idea, but it's not completely correct. Note that all we have is
p ( x ) = A ( x ) × ∏ ( x − i ) + 1
for some (possibly constant) polynomial.
A cleaner argument is to start off with de g p < 1 0 0 from the non-trivial factorization, and then show that in this case de g p ≥ 1 0 0 .
Problem Loading...
Note Loading...
Set Loading...
If this factorization were possible, we could find A ( x ) , B ( x ) ∈ Z [ x ] , both with degrees less than 1 0 0 , such that A ( x ) B ( x ) ≡ j = 1 ∏ 1 0 0 ( x − j ) − 1 and hence A ( j ) B ( j ) = − 1 1 ≤ j ≤ 1 0 0 Thus we can find ϵ j ∈ { − 1 , 1 } for 1 ≤ j ≤ 1 0 0 such that A ( j ) = ϵ j B ( j ) = − ϵ j 1 ≤ j ≤ 1 0 0 so that A ( j ) + B ( j ) = 0 for 1 ≤ j ≤ 1 0 0 . Thus A ( x ) + B ( x ) is a polynomial of degree at most 9 9 with at least 1 0 0 distinct zeros, and hence is identically zero. Thus B ( x ) ≡ − A ( x ) , and so − A ( x ) 2 ≡ j = 1 ∏ 1 0 0 ( x − j ) − 1 Putting x = 1 0 1 , this would imply that 1 0 0 ! − 1 = − A ( 1 0 1 ) 2 was negative, which is nonsense. Thus no such factorization exists.